Nanoparticulate Perovskites for Photocatalytic Water Reduction - Sven A. Freimann; Catherine E. Housecroft; Edwin C. Constable (Nanomaterials, 2023)
SrTiO3 and BaTiO3 nanoparticles (NPs) were activated using H2O2 or aqueous HNO3, and pristine and activated NPs were functionalized with a 2,2′-bipyridine phosphonic acid anchoring ligand (1), followed by reaction with RuCl3.3H2O and bpy, RhCl3.3H2O and bpy, or RuCl3.3H2O. The surface-bound metal complex functionalized NPs were used for the photogeneration of H2 from water, and their activity was compared to related systems using TiO2 NPs. The role of pH during surface complexation was found to be important. The NPs were characterized using Fourier transform infrared (FTIR) and solid-state absorption spectroscopies, thermogravimetric analysis mass spectrometry (TGA-MS), and matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), and the dihydrogen generation was analyzed using gas chromatography–mass spectrometry (GC-MS). Our findings indicate that extensively functionalized SrTiO3 or BaTiO3 NPs may perform better than TiO2 NPs for water reduction.